(g − 2) μ versus K → π + E miss induced by the (B − L)23 boson - Zhaofeng Kang (Journal of High Energy Physics, 2021)
Abstract To address the long-standing (g − 2) μ anomaly via a light boson, in ref. [1] we proposed to extend the standard model (SM) by the local (B − L)23, under which only the second and third generations of fermions are charged. It predicts an invisible Z′ with mass O 100 $$ \mathcal{O}(100) $$ MeV, and moreover it has flavor-changing neutral current (FCNC) couplings to the up-type quarks at tree level. Such a Z′, via K L → π 0 + Z′(→ v v ¯ $$ v\overline{v} $$ ) at loop level, may be a natural candidate to account for the recent KOTO anomaly. In this article, we investigate this possibility, to find that Z′ can readily do this job if it is no longer responsible for the (g − 2) μ anomaly. We further find that both anomalies can be explained with moderate tuning of the CP violation, but may contradict the B meson decays.